PENGARUH IKLAN DALAM PASAR PERSAINGAN MONOPOLISTIK DAN OLIGOPLI DI INDONESIA - Evi Suryani Harahap; Siti Handayani; Nurul Hasanah; Nafthalia Panjaitan; Agnes Laura Simanjuntak (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2026)
Advertising is one of the marketing strategies that plays an important role in influencing consumer behavior and increasing a company's competitiveness in the market. In monopolistic competition and oligopoly market structures, advertising activities are often used by companies to build brand image, create product differentiation, and attract consumer interest in the products offered. This study aims to analyze the influence of advertising in monopolistic competition and oligopoly markets in Indonesia. The research method used in this study is a literature review by examining various relevant scientific articles from reputable national journals published in recent years. Data collection techniques were carried out through the exploration of various literature sources related to advertising, consumer behavior, and market structure. The results of the study show that advertising has a significant influence on increasing brand awareness, shaping consumer perceptions, and encouraging purchasing decisions for a product. In addition, in monopolistic competition markets, advertising plays a role in creating product differentiation and increasing consumer loyalty, while in oligopoly markets advertising functions as a strategy to maintain the company's position and increase competitiveness among companies. Therefore, advertising activities are an important instrument in marketing strategies that can influence consumer behavior and strengthen a company's position in market competition.